Efficacy of fungicides and antibiotics on seed mycoflora and seed germination of some species - and KANAK MANJARI, BHARAT RAI, S. JARIWALA (Indian Phytopathology, 2002)
The effects of different concentrations of 4 fungicides, Bavistin [carbendazim], Dithane M-45 [mancozeb], Agrosan G N [phenylmercury acetate] and PCNB [quintozene] and 2 antibiotics, griseofulvin and mycostatin, on the seed mycoflora and seed germination of 3 spices, fennel (Foeniculum vulgare), black caraway (Bunium persicum) and ammi (Trachyspermum ammi), were studied in vitro. All the fungicides and antibiotics were found to be effective in reducing the seed mycoflora both qualitatively and quantitatively. The percentage germination of all the fungicide treated seeds was higher than that of untreated ones except in the case of Agrosan G N, whereas both the antibiotics exhibited a phytotoxic effect on seed germination.